What is the effectiveness of titanium tetrafluoride to prevent or treat dental caries and tooth erosion? A systematic review. (18th August 2022) - Chevitarese, Ana Beatriz; França Leite, Karla Lorene de; Marañón-Vásquez, Guido A.; Masterson, Danielle; Pithon, Matheus; Maia, Lucianne Cople
Abstract: Objectives: Answer the question: What is the effectiveness of titanium tetrafluoride (TiF4 ) when compared to other fluorides, placebo solution or a negative control to prevent or treat dental caries and tooth erosion? Materials and methods: This review is in accordance with PRISMA guidelines. In vivo and in situ studies that used TiF4 over enamel or dentine were included. Electronic searches were conducted on MEDLINE, Scopus, Embase, WOS, Cochrane Library, VLH, Clinical Trials and OpenGrey. Risk of bias (ROB) assessments used RoB2 and ROBINS-I for randomized and non-randomized controlled trials (RCTs and on-RCTs); Syrcle's ROB tool for animal studies; and a modified tool proposed by Hollanders for in situ studies. Results: A total of 28 studies met the eligibility criteria. From these, 6 were in humans (3 RCT and 3 Non-RCT); 4 were in animals and 18 were in situ. For in vivo studies, all RCTs have some concerns related to ROB and all of the non-RCT studies were classified as with serious risk. One animal study had a low and three a high ROB. Regarding in situ studies, seven had a low, ten had an average and only one had a high ROB. The certainty of the evidence (GRADE) ranged from moderate to very low. Conclusions: Although most of the results suggest a positive effect of TiF4 on the prevention and treatment of caries and dental erosion, it is not possible to have definitive conclusions due to the high studies' methodological heterogeneity, and the low quality of evidence for most outcomes. Registration: The protocol of this syste. atic review was registered in the OPEN SCIENCE FRAMEWORK database (osf.io/6dgs9) DOI:10.17605/OSF.IO/KUZA7 on 6 August 2020.